Analisis Al-Urf dalam Hukum Islam terhadap Pelaksanaan Perkawinan Adat Nokolontigi dan Mandiupasili Dalam Perkawinan Suku Adat Kaili Kelurahan Kabonena Kecematan Ulujadi Sulawesi Tengah - Andiahmad Ramadhani; M. Abdurahman; Encep Abdul Rojak (UNISBA Press, 2025)
Abstract. Indonesia is an archipelago country because it consists of thousands of islands and has various tribes and different customs. Differences in place of residence also distinguish variations in the livelihoods of customs and habits of the community. Customs or traditions are often defined as regulations that apply in a particular society, and include various norms that govern life together. The concept of